BPMN extensions for automating cloud environments using a two-layer orchestration approach. (August 2018) - Dukaric, Robert; Juric, Matjaz B.
Highlights: We provide support for cloud-specific workflows in BPMN business process engines. We define a meta-model for modeling cloud workflows. We extend BPMN 2.0.2 specification to orchestrate cloud-specific workflows. We implement a meta-model using BPMN extensions. We measure process size and complexity of two process models using various metrics. Abstract: Cloud orchestration describes the automated arrangement, coordination, and management of complex cloud systems, middleware and services, and is realized by orchestrating workflows. To achieve an end-to-end cloud orchestration, workflow designers usually have to cope with integration challenges between two different technologies – one that entails technical cloud orchestration and another comprising business-level orchestration. This however presents a complex undertaking for workflow designers, as they have to gain sufficient knowledge and expertise of two diverse technologies in order to automate cloud-specific tasks across two different domains. Introduction of a unified orchestration platform would solve these issues, as it would deliver a common vocabulary for different types of workflow designers and would provide them with a single platform for orchestrating both business and technical activities, without having to face the integration complexities. The main objective of this paper is to provide support for cloud-specific workflows in BPMN business process engines. To achieve this objective we (1) define a meta-model for modeling cloud workflows, (2) extend BPMN 2.0.2 specification to orchestrate cloud-specific workflow activities, and (3) implement a meta-model with BPMN extensions by showing how cloud orchestration workflow elements (i.e. activities and workflow control) map onto extended BPMN elements. As a part of the evaluation we measure process size and complexity of two process models using various process metrics. The results have shown that when using our proposed BPMN extensions, the overall size and complexity of the use case process under test has been reduced by more than half on an average. We also improve the readability of BPMN process.